Strategy of Entrepreneurship & Creative Economy Development through District Mapping in Bandung City - Fiki Chikara Satari; Nabila As’ad (ITB Journal Publisher, LPPM ITB, 2018)
Since Bandung joined the UNESCO Creative Cities Network (UCCN) on 11 December 2015, all its stakeholders and the city have become more active in fulfilling its commitments as a City of Design, among others by strengthening existing data on creative economy entrepreneurs and their impact on welfare improvement. A previous research conducted by the Economy Department of Bandung Municipality mapped thousands of creative economy actors spread over 30 districts in Bandung. However, it was necessary to further identify these actors and their roles in order to be able to build a strategy around creative economy development in Bandung, which was the main aim of this research. The ecosystem of five creative economy subsectors in selected districts was mapped. The results are presented here as a reference for building strategies for creative-potential based community development and policy making.